2014
DOI: 10.1155/2014/535308
|View full text |Cite
|
Sign up to set email alerts
|

Smart Grid as a Service: A Discussion on Design Issues

Abstract: Smart grid allows the integration of distributed renewable energy resources into the conventional electricity distribution power grid such that the goals of reduction in power cost and in environment pollution can be met through an intelligent and efficient matching between power generators and power loads. Currently, this rapidly developing infrastructure is not as “smart” as it should be because of the lack of a flexible, scalable, and adaptive structure. As a solution, this work proposes smart grid as a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Cloud computing has different models to provide the smart grid services and the utilities requirements, as below: Public cloud: A simple and more cost‐effective model of the cloud computing to which the accession is unrestrained for all the users. In this virtual environment, various service providers make offers to sell specific applications or other cloud services, such as storage or virtual machines.…”
Section: Cloud Computing Application For the Smart Gridmentioning
confidence: 99%
“…Cloud computing has different models to provide the smart grid services and the utilities requirements, as below: Public cloud: A simple and more cost‐effective model of the cloud computing to which the accession is unrestrained for all the users. In this virtual environment, various service providers make offers to sell specific applications or other cloud services, such as storage or virtual machines.…”
Section: Cloud Computing Application For the Smart Gridmentioning
confidence: 99%
“…Although RES technology is not able to cope with the demand of electricity consumption these days, integrating it with the existing power grid has shown that it is able to change the system towards certain extent [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…A new type of business entity known as an aggregator can act as a bridge between power system operators and consumers [19][20][21] by installing the required infrastructure for appliance control at the consumer premises, and trade the available capacity with the TSO. Aggregator consumer commitments are covered by a service level agreement (SLA) between two parties [22,23], with the aggregators delivering the service provided by the BRP by reducing the load based on the application of DR on consumer controllable loads. An illustration of aggregators playing the role of BRPs is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%